2014
DOI: 10.1039/c3ce42349b
|View full text |Cite
|
Sign up to set email alerts
|

Phase formation, morphology evolution and tunable bandgap of Sn1−xSbxSe nanocrystals

Abstract: The phase formation, morphology evolution and bandgap of Sn1−xSbxSe (0 ≤ x ≤ 0.6) nanocrystals synthesized at 230–275 °C for 5–36 h in a one-pot system were studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…3, the direct bandgaps of Ge-and Sb-doped SnS films are in the range of 1.25-1.35 and 1.30-1.39 eV, respectively, which are obtained from their reflectance spectra by performing the Kubelka-Munk transformation [17,18], showing that the direct bandgaps increase with the Ge and Sb concentrations, respectively. The similar trend was also observed in the Sn 1 − x Sb x Se [15] and Sn x Ge 1 − x Se alloys [19]. The direct bandgaps of SnS, GeS, and Sb 2 S 3 are about 1.3, 1.6, and 1.5-1.6 eV, respectively [1,10,20].…”
Section: Tunable Bandgaps Of Ge-and Sb-doped Sns Filmssupporting
confidence: 76%
See 1 more Smart Citation
“…3, the direct bandgaps of Ge-and Sb-doped SnS films are in the range of 1.25-1.35 and 1.30-1.39 eV, respectively, which are obtained from their reflectance spectra by performing the Kubelka-Munk transformation [17,18], showing that the direct bandgaps increase with the Ge and Sb concentrations, respectively. The similar trend was also observed in the Sn 1 − x Sb x Se [15] and Sn x Ge 1 − x Se alloys [19]. The direct bandgaps of SnS, GeS, and Sb 2 S 3 are about 1.3, 1.6, and 1.5-1.6 eV, respectively [1,10,20].…”
Section: Tunable Bandgaps Of Ge-and Sb-doped Sns Filmssupporting
confidence: 76%
“…However, our previous studies showed that the bandgap of Sn 1 − x Sb x Se nanocrystals increases with the Sb concentration (x) in the range of 0.1-0.2 [15]. Therefore, further exploration on the synthesis and characterization of cation-doped SnS is still attractive.…”
Section: Introductionmentioning
confidence: 93%
“…And this slight difference satisfies the criterion for substitution solubility proposed by Hume-Rothery who pointed out that an extensive solid solubility of one metal in another only occurs if the diameter of the atoms differs by less than 15%. 20 Furthermore, the calculated unit cell volume of the (Sn x Sb 1Àx ) 2 Se 3 crystals gradually increases from 545.23 Å 3 (x = 0.00) to 546.53 Å 3 (x = 0.10), and this increase is known to occur due to doping. 21 Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, n -type single crystals of 6 mol % Bi-doped SnSe have been reported to show a high ZT of 2.2 . To date, few nanostructures (e.g., nanowires, nanoplates, nanoflowers, and nanosheets) of SnSe have been synthesized by bottom-up wet chemical synthesis, , but the materials are mostly p -type. , Recently, electronic transport properties of n -type Cl-doped SnSe nanoparticles have been studied, which show moderate power factors . Thus, n -type SnSe with 2D few-layered nanosheet morphology would be interesting for thermoelectric investigations as it may exhibit low κ L due to excess phonon scattering from nanoscale grains and interfaces.…”
mentioning
confidence: 99%